2014
DOI: 10.1073/pnas.1416940111
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane treatment of autism spectrum disorder (ASD)

Abstract: Autism spectrum disorder (ASD), characterized by both impaired communication and social interaction, and by stereotypic behavior, affects about 1 in 68, predominantly males. The medicoeconomic burdens of ASD are enormous, and no recognized treatment targets the core features of ASD. In a placebo-controlled, double-blind, randomized trial, young men (aged 13-27) with moderate to severe ASD received the phytochemical sulforaphane (n = 29)-derived from broccoli sprout extracts-or indistinguishable placebo (n = 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
274
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(286 citation statements)
references
References 33 publications
8
274
2
2
Order By: Relevance
“…Glucosinolates and isothiocyanates could be interesting candidates for such strategies. They have been investigated in clinical trials with no significant reported toxicity (31)(32)(33). However, only sulforaphane precursors such as purified glucosinolates or broccoli sprouts and not sulforaphane are currently in intervention trials because sulforaphane is highly unstable in its free form (34).…”
Section: Introductionmentioning
confidence: 99%
“…Glucosinolates and isothiocyanates could be interesting candidates for such strategies. They have been investigated in clinical trials with no significant reported toxicity (31)(32)(33). However, only sulforaphane precursors such as purified glucosinolates or broccoli sprouts and not sulforaphane are currently in intervention trials because sulforaphane is highly unstable in its free form (34).…”
Section: Introductionmentioning
confidence: 99%
“…These SRS and ABC scores were greater than the scores of ASD individuals with an age range of 13-27 years (SRS, 120.12; ABC, 60.14) [22]. Other evaluations, including an ophthalmologic examination and dental …”
Section: Psychometric Evaluationmentioning
confidence: 72%
“…It is a follow-up to a prior report [1] which described the beginning of this Study using a combination strategy which we will shortly but briefly review below. That Study by Evans and Fuller in turn was initiated and prompted by yet a prior clinical trial [2] providing a simple, safe, over-the-counter food supplement, which yielded significant positive outcomes after a 18-week period.…”
Section: Introductionmentioning
confidence: 99%